Pengaruh Fraud Triangle Terhadap Manajemen Laba Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Fitria Eka Ningsih (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to analyze the influence of fraud triangle on earnings management. Fraud triangle theory proposed by Cressey states that there are three conditions that become risk factors of fraud namely pressure, opportunity and rationalization. To examine the occurrence of earnings management, this study proposes a variable that is the proxy size of the three components of the fraud triangle, as listed in SAS No. 99 of personal financial need, external pressure, and financial targets as a measure of the pressure component, ineffective monitoring as a measure of the component of opportunity, and component rationalization. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2018-2021. Purposive sampling method used in sampling so that obtained by research data as many as 21 companies. The study used secondary data obtained from the annual report of manufacturing companies listed on the BEI in 2018-2021. Method of testing the hypothesis in this study using multiple linear regression method. The results showed that personal financial need variables proxied with stock ownership ratio, ineffective monitoring variables proxyed by the number of audit committees, the rationalization variables proxied by the Dividend Payout Ratio have no effect on earnings management. While the external pressure variables proxyed by Debt To Equity Ratio and Return On Asset, ineffective monitoring variables proxied by the proportion of independent board of commissioners have an influence on earnings management.